Effects of EPs 7630 on Illness Absence from Childcare or School due to Acute Bronchitis—A Meta-analysis - Zwiauer, Karl; Funk, Petra; Zimmermann, Andrea; Lehmacher, Walter; Kamin, Wolfgang (Journal of Pediatric Infectious Diseases, 2024)
Objective In the pediatric population, acute bronchitis (AB) is a leading cause of illness absence from childcare, school, or apprenticeship. We report a meta-analysis of double-blind, randomized trials with children and adolescents with AB (aged 1–18 years), who were treated with Pelargonium extract EPs 7630 or placebo for 7 days.Methods The average number of days absent from childcare, school, or apprenticeship due to illness and the proportion of patients still unable to return to their normal activities at treatment end were assessed.Results Literature search identified two eligible trials with a total of 420 patients. Illness absence was reported for all but two patients under placebo at baseline and for 46.7% (EPs 7630) and 85.0% (placebo) of patients at day 7. Meta-analysis risk ratio for absence at day 7 was 0.55 (95% confidence interval: 0.47, 0.64) for all patients, 0.59 (0.46, 0.76) for children younger than 6 years, and 0.53 (0.44, 0.64) for participants aged 6 to 18 years, all favoring EPs 7630. Compared with placebo, average time until return to normal activities was reduced by EPs 7630 by 1.51 (1.16, 1.86) days for all subjects, by 1.50 (0.92, 20.7) days for those younger than 6 years, and by 1.54 (1.11, 1.97) days for those 6 to 18 years of age (p < 0.001 favoring EPs 7630 for all treatment group comparisons shown).Conclusion For children and adolescents with AB, meta-analysis shows that EPs 7630 treatment for 7 days significantly reduces the average time of illness absence and significantly increases the proportion of patients able to return to normal activities within 1 week.
Keywords: acute bronchitis; adolescent; child; Pelargonium; extracts